2006
DOI: 10.1143/jjap.45.8364
|View full text |Cite
|
Sign up to set email alerts
|

Optical Emission Spectrometry of Plasma in Low-Damage Sub-100 nm Tungsten Gate Reactive Ion Etching Process for Compound Semiconductor Transistors

Abstract: In this study, we investigate in situ optical emission spectra from plasma in the reactive ion etching (RIE) of tungsten, a suitable candidate for gate metallization in compound-semiconductor-based high-mobility channel devices. This results in a detailed understanding of the effects of etching parameters vital to reducing etch induced damage and improving etching performance. A SF6 based chemistry was used with other functional gases, such as N2, O2, and CHF3. Van de Pauw (VdP) structures on GaAs based high e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…For instance, it has been demonstrated that ion beam-assisted etching consumes at least 10 nm of wet-etched GaAs to produce a stoichiometric surface, rendering this approach unsuitable for the fabrication of devices with atomic depth resolution. Reactive ion beam etching was used for dry etching of GaAs and AlGaAs, and despite fabricating relatively smooth surfaces, ion-induced surface damage appeared unavoidable . To address this problem, GaAs chlorine radical etching without ion bombardment was proposed, although etching rates between 3 nm/min and 10 μm/min were possible only when samples were heated in the range of 300–400 °C .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, it has been demonstrated that ion beam-assisted etching consumes at least 10 nm of wet-etched GaAs to produce a stoichiometric surface, rendering this approach unsuitable for the fabrication of devices with atomic depth resolution. Reactive ion beam etching was used for dry etching of GaAs and AlGaAs, and despite fabricating relatively smooth surfaces, ion-induced surface damage appeared unavoidable . To address this problem, GaAs chlorine radical etching without ion bombardment was proposed, although etching rates between 3 nm/min and 10 μm/min were possible only when samples were heated in the range of 300–400 °C .…”
Section: Introductionmentioning
confidence: 99%
“…Reactive ion beam etching was used for dry etching of GaAs and AlGaAs, and despite fabricating relatively smooth surfaces, 8 ion-induced surface damage appeared unavoidable. 9 To address this problem, GaAs chlorine radical etching without ion bombardment was proposed, although etching rates between 3 nm/min and 10 μm/min were possible only when samples were heated in the range of 300−400 °C. 10 In an electron beam excited plasma system, the surface of GaAs was bombarded sequentially using Ar ions in the presence of Cl 2 or Cl.…”
Section: Introductionmentioning
confidence: 99%
“…with a peak at 289.3 nm should have then been observed 31,32 ), the multi-step dissociation seems to be complete. However a really weak and broad band at 200-250 nm could be related either to SF6 dissociation species 33 or to SOat 258 nm 34 , which are probably due to interaction of sulfur species with the reactor walls. On the contrary, in pure CHF3 plasma Selectivity was also studied under the same conditions for conventional resists.…”
Section: Fluorinated Plasma Characterizationmentioning
confidence: 99%